Mitigating Norway spruce mortality through the combined use of an anti-attractant for Ips typographus and an attractant for Thanasimus formicarius - Korolyova, Nataliya; Bláha, Jaromír; Hradecký, Jaromír; Kašpar, Jaroslav; Dvořáková, Barbora; Jakuš, Rastislav (Frontiers in Forests and Global Change, 2024)
This study investigates the efficacy of combined treatment strategy, incorporating pheromones for bark beetle I. typographus (IT) and attractant of its natural enemy T. formicarius (TF), along with anti-attractants for IT (containing 1-hexanol, 1-octen-3-ol, 3-octanol, eucalyptol, trans-thujanol, and trans-conophthorin), to enhance protection methods for Picea abies against biotic disturbances. Two field experiments – trapping experiment and tree protection experiment – were conducted in June 2023 in managed spruce-dominated beetle-affected stands in Czechia. We anticipated higher catches of IT in traps baited with IT pheromone (containing s-ipsdienol, s-cis-verbenol, and 2-methyl-3-buten-2-ol) and TF attractant compared to traps using IT pheromone alone, since compounds intrinsic to IT pheromone, namely 2-methyl-3-buten-2-ol, ipsenol, and ipsdienol, are integral components of the attractant designed for TF. We hypothesized that application of TF attractant and IT anti-attractant would enhance the treatment’s protective properties, assuming that attracted TF would function as a predator, reducing bark beetle population and increasing tree survival rates. Semiochemical composition declared by the producers was verified using gas chromatography-mass spectrometry analysis. In the trapping experiment, EcoTrap-type traps were baited with six combinations of lures and anti-attractant. In the tree protection experiment, 28 mature Norway spruce trees situated at newly created forest edges underwent four treatment types: TF attractant, IT anti-attractant, their combination, and no treatment (“control”). Traps baited solely with TF attractant did not capture either beetle, whereas traps lured with IT pheromone, TF attractants and anti-attractant showed no captures of IT but recorded the highest numbers of TF, suggesting significant potential for combined treatment efficacy. Surprisingly, tree mortality was observed exclusively among trees treated only with TF pheromone and in their vicinity, suggesting unique bark beetles’ response to the mixture of predator’s attractant and host tree kairomones, a phenomenon that was not previously reported. Application of anti-attractant and TF treatment effectively prevented tree mortality, demonstrating the repellent potential of IT anti-attractant against bark beetles. However, mortality rates showed no significant differences among control trees, those treated with anti-attractants, or those treated with the combination of anti-attractants and TF attractant, underscoring necessity for further research to optimize treatment efficacy.